Targeted Protein Degradation: Design Considerations for PROTAC Development. Issue 12 (5th December 2022) - Tran, Nathan L.; Leconte, Georges A.; Ferguson, Fleur M.
Abstract: Targeted protein degradation has recently gained widespread interest as both a novel therapeutic strategy and a useful tool in biomedical research. Targeted protein degraders are often sub‐stoichiometric and do not require strong binding affinity for their targets, enabling access to previously inaccessible targets. Proteolysis‐targeting chimeras (PROTACs) are one class of targeted protein degraders that promote degradation by recruiting a target protein to an E3‐ligase complex via a heterobifunctional molecule. The modular nature of PROTACs allows for their rational design and systematic optimization. Here we suggest resources and methodologies for developing PROTAC degraders for researchers that may be new to the field. © 2022 Wiley Periodicals LLC.